Superior Effects of Eccentric to Concentric Knee Extensor Resistance Training on Physical Fitness, Insulin Sensitivity and Lipid Profiles of Elderly Men - Chen, Trevor Chung-Ching; Tseng, Wei-Chin; Huang, Guan-Ling; Chen, Hsin-Lian; Tseng, Kuo-Wei; Nosaka, Kazunori (Frontiers in Physiology, 2017)
It has been reported that eccentric training of knee extensors is effective for improving blood insulin sensitivity and lipid profiles to a greater extent than concentric training in young women. However, it is not known whether this is also the case for elderly individuals. Thus, the present study tested the hypothesis that eccentric training of the knee extensors would improve physical function and health parameters (e.g. blood lipid profiles) of older adults better than concentric training. Healthy elderly men (60-76 y) were assigned to either eccentric training or concentric training group (n=13/group), and performed 30-60 eccentric or concentric contractions of knee extensors once a week. The intensity was progressively increased over 12 weeks from 10% to 100% of maximal concentric strength for eccentric training and from 50% to 100% for concentric training. Outcome measures were taken before and 4 days after the training period. The results showed that no sings of muscle damage were observed after any sessions. Functional physical fitness (e.g., 30-s chair stand) and maximal concentric contraction strength of the knee extensors increased greater (P≤0.05) after eccentric training than concentric training. Homeostasis model assessment, oral glucose tolerance test and whole blood glycosylated hemoglobin showed improvement of insulin sensitivity only after eccentric training (P≤0.05). Greater (P≤0.05) decreases in fasting triacylglycerols, total and low-density lipoprotein cholesterols were evident after eccentric training than concentric training, and high-density lipoprotein cholesterols increased only after eccentric training. These results support the hypothesis and suggest that it is better to focus on eccentric contractions in exercise medicine. Keywords: muscle damage, lengthening muscle contraction, senior functional fitness tests, insulin resistance, blood lipid profile